2022
DOI: 10.3390/ijerph191811550
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Emotional Distress, Sleep Changes, Decreased Tooth Brushing Frequency, Self-Reported Oral Ulcers and SARS-Cov-2 Infection during the First Wave of the COVID-19 Pandemic: A Global Survey

Abstract: This study assessed the association between emotional distress, sleep changes, decreased frequency of tooth brushing, and self-reported oral ulcers, and the association between COVID-19 status and decreased frequency of tooth brushing. Using a cross-sectional online survey, data were collected from adults in 152 countries between July and December 2020. Binary logistic regression analyses were conducted to determine the associations between dependent (decreased frequency of tooth brushing, oral ulcers, change … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 75 publications
0
14
0
Order By: Relevance
“…Some studies have concluded that poor toothbrushing may increase the risk of COVID-19 . Second, COVID-19–associated psychological distress may change oral health–related behaviors . Psychological distress caused by depression, loneliness, and suicidal ideation is known to be associated with a lower frequency of toothbrushing.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Some studies have concluded that poor toothbrushing may increase the risk of COVID-19 . Second, COVID-19–associated psychological distress may change oral health–related behaviors . Psychological distress caused by depression, loneliness, and suicidal ideation is known to be associated with a lower frequency of toothbrushing.…”
Section: Discussionmentioning
confidence: 99%
“… 27 , 28 Second, COVID-19–associated psychological distress may change oral health–related behaviors. 11 , 29 Psychological distress caused by depression, 30 loneliness, and suicidal ideation 31 is known to be associated with a lower frequency of toothbrushing. Because social isolation increased during the pandemic lockdown, emotional distress increased, which may have negatively affected toothbrushing frequency.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Self-report questionnaires have acceptable validity and can be used for epidemiological studies regarding the surveillance of PD because they are less demanding in terms of cost and time and can be supplemental in the evaluation of the association between PD and other conditions [41][42][43][44]. The choice to apply a self-report questionnaire to communicate the periodontal conditions of a population makes sense within public health settings when the conditions for a clinical evaluation, such as periodontal probing, is not possible, as happened in the COVID-19 pandemic emergency [45][46][47][48][49].…”
Section: Introductionmentioning
confidence: 99%